Analysis of the Impact of the Implementation of Special Needs School Entrepreneurship Education on Institutional Sustainability - Caecilia Winarni; Maria R. Nindita Radyati; Maria Ariesta Utha (International Journal Labs, 2023)
The COVID-19 pandemic has changed the world and affected world economic growth which has caused a world economic crisis that has caused an increase in the level of extreme poverty in the world. Efforts to restore world economic growth and sustainability by implementing an action plan with world leaders on the Sustainable Development Goals (SDGs) as a global agreement for sustainability. Special attention to the poor, vulnerable, marginalized and persons with disabilities (SDGs no. 1) which includes all areas of life both in the field of Health (SDGs no.3), the field of continuing education (SDGs no. 4), employment opportunities (SDGs no. 8) as well as the use of public facilities and services and the internet for the sustainability of their lives. The purpose of this study is to analyze, the social impact and linkage of School Entrepreneurship Implementation in SKh on SDGs no1, 4,8,9,10,12,16. The research method used in this study is the descriptive quantifier method). The sample of 34 consisted of 17 stakeholders for each unit. Purposive sampling techniques Data collection methods with Google Forms and structured interviews with principals, parents and school partners to get in-depth information from stakeholders. The analysis method using content analysis is strengthened by SROI analysis. Implementation in December 2022. Based on the SROI Analysis and respondents' answers the impact of the Implementation of the Entrepreneurship Education Curriculum in SKh is very large on the sustainability of the Institution. The implementation of the entrepreneurship curriculum in this school increases productivity and partnership with the community to build an inclusive learning ecosystem and an entrepreneurial ecosystem. Project Based Learning allows teachers and students to develop together and form a learning ecosystem. Group activities improve student productivity and skills as Krüger argues about co-production and Co-innovation. Schools need to establish communication and partnerships with the community and the business world to improve the quality competence of graduates and the competence of human resources in the institution, school promotion, product marketing and fundraising.